Analysis Of Difficulties in Learning Nahwu in Students: Literature Study - Susanto,; Muhammad Samin, Saproni (Perspektif Pendidikan dan Keguruan, 2025)
This study aimed to analyze difficulties in learning nahwu among students through a literature study. The research method used a qualitative approach with library research that examined various scientific sources related to difficulties in learning nahwu, from journal articles, theses, and other academic literature. Data were analyzed through data reduction, thematic data presentation, and conclusion drawing with source triangulation. The research results showed that difficulties in learning nahwu among students were caused by five main factors: (1) lack of comprehensive understanding of nahwu concepts, (2) difficulties in memorizing and understanding sentence structures, (3) lack of practice in using Arabic language, (4) lack of motivation and interest in learning nahwu, and (5) lack of using self-directed learning approaches. The solutions offered included improving understanding of nahwu concepts through effective teaching, enhancing the ability to memorize sentence structures through intensive practice, increasing Arabic language practice through interactive activities, improving motivation through engaging teaching methods, and enhancing student self-directed learning. The conclusion of this research can contribute to the development of more effective and applicable nahwu learning strategies for students.